The relationship between belonging motivation and emotional attention in the performance of the spiking and blocking skills in female volleyball. - Abbas, Asst.L. Noor Ayad; Rashid, L.Dr. Maryam Abdul-Amir; Jawda, Asst.L.Murtaza Ali (Sulaimani Journal for Humanities, 2026)
This study aimed to identify the values of belonging motivation and emotional attention and their relationship to the performance of the spiking and blocking skills in volleyball among female students. The research hypotheses were: there is a statistically significant correlation between belonging motivation and the performance of the spiking and blocking skills in volleyball among female students, and there is a statistically significant correlation between emotional attention and the performance of the spiking and blocking skills in volleyball among female students. The researchers used a descriptive approach through correlational studies on a group of third-year female students at the College of Physical Education and Sports Sciences for Girls at the University of Baghdad. The researchers administered the belonging motivation scale, the emotional attention scale, the spiking test, and the blocking test in volleyball to the study sample. Then, the researchers used appropriate statistical methods to extract the results. Based on these results, they reached several conclusions, including that emotional attention is related to improving the spiking and blocking skills in volleyball among female students, and that belonging motivation is related to emotional attention. The ability to focus on specific skills that motivate students to engage with them effectively is limited, thus increasing their motivation to achieve their shared goals. Based on these findings, the researchers recommend focusing on measuring and evaluating the cognitive abilities of students in the Faculty of Physical Education and Sports Sciences, specifically emotional attention and motivation to belong, as these factors are related to improving students' skills, particularly the slam slam and blocking skills.
Keywords: Belonging motivation; emotional attention; crushing blow; defensive wall